La música ecuatoriana en el proceso de enseñanza-aprendizaje de los estudiantes de quinto, sexto y séptimo años de educación general básica de la escuela Manuel Carrión Pinzano del cantón Quilanga. Periodo 2014-2015 - Bravo Álvarez, Paulo David (2016)
This research work has been an essential part in the musical development of students, which had as general objective, determine the level of knowledge of our Ecuadorian music with fifth-, sixth and seventh year of basic education school Manuel Carrión Pinzano Quilanga canton, through knowledge of Ecuadorian musical genres in order to strengthen the musical cultural identity. For compliance, we worked with the universe population of 94 people and data collection and information was carried out using techniques and research tools (survey, interview), the survey was applied to 13 teachers, an interview with the school principal to 80 children of the institution were given a survey; Once the information is the process by Microsoft Excel for charts and tables that allowed us to get the results and draw the conclusions and recommendations; according to the results we can say that 100% of the population, claim that the realization of an Ecuadorian music festival contributes to the development and rescue of our music; in this context as proposed Prime Ecuadorian music festival takes place in Manuel Carrión Pinzano school, with students in fifth, sixth and seventh years of basic education in the canton Quilanga. It is concluded that cultural roots are forgotten, because the students are considered as consumers of foreign music, losing interest in the Ecuadorian music and behind them the loss of musical artistic values observed, so is considers important to strengthen the music within the curriculum of study of each school, as it allows to discover and develop rhythmic music-listening skills of children and especially rescue artistic and human values. On the other hand it is recommended that the authorities of this institution, maintain and strengthen the instrumental group and spaces as a means of enjoyment and learning so that it can enrich the musical knowledge of the students in their education